Kolorystyka szczegółów geograficznych w Notitia dignitatum pars orientis według rękopisów Oxoniensis Canonicianus misc. 378 i monacensis latinus 10291 - Jacek Wiewiorowski (Vox Patrum, 2018)
The text analyses the reality of the colours used in the topographical allusions of the insignia of late Roman officials, known from the Notitia dignitatum in partibus Orientis from the turn of the 5th century, preserved in Oxoniensis Canonicianus Misc. 378 and Monacensis Latinus 10291 - Not. Dig. Or. 28, 29, 31, 34, 36, 38, 39, 37. The author links the accuracy of colours used by the illustrators of the insignia with the intention of the Notitia dignitatum to give the emperor and other members of late Roman elite a relatively coherent picture of the geographically remote regions of the Eastern Roman Empire. He subsequently relates it to the functioning of human brain as a pattern recognizer shared universally by human beings, despite that colour perception among Humans is strongly affected by culture and calling for the inclusion of data collected by evolutionary psychology and other evolutionary research in historical studies.